Verification and validation of a CFD model of a fixed regenerator for heat recovery from air - Penev, Angel; Tsokov, Lyubomir; Vassilev, Momchil (E3S web of conferences, 2021)
The article presents verification and validation of a numerical model of conjugated heat and mass transfer processes and aerodynamics in a fixed "honeycomb" type regenerator with square channels for heat recovery from the exhaust air of a local ventilation system. The processes in the regenerator are simulated by the CFD method. The influence of the processes of condensation and evaporation of moisture in the humid air on the efficiency of the regenerator has been investigated through these simulations and is shown in the article. The calculations of the fixed regenerator's thermal efficiency and pressure losses are made by known analytical models and the results are compared with those of the numerical model. The article compares the model simulation results with experimental data and data from reference sources.